2021
DOI: 10.1021/acsenergylett.0c02575
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Insertion of I–Cl Interhalogen in a Graphite Cathode for Aqueous Dual-Ion Batteries

Abstract: Anion storage in cathode of dual-ion batteries provides leeway for new battery chemistries. For high energy density and better safety, it is desirable but challenging to reversibly intercalate chloride in a graphite cathode because either the oxygen or chlorine evolution reaction can prevail over chloride insertion. The primary barrier is the lack of suitable aqueous electrolytes that suppress these parasitic reactions. Herein, we report an aqueous deep eutectic solvent gel electrolyte that allows reversible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…5(d) ). The third peak at 202.1 eV shows the existence of C–Cl bonds 33 and indeed this also correlates with the C–Cl vibrational frequency shift observed with the corresponding FT-IR results.…”
Section: Resultssupporting
confidence: 80%
“…5(d) ). The third peak at 202.1 eV shows the existence of C–Cl bonds 33 and indeed this also correlates with the C–Cl vibrational frequency shift observed with the corresponding FT-IR results.…”
Section: Resultssupporting
confidence: 80%
“…It can be observed that the intensity of the carbon peak (26.7°) becomes weaker after fully charging and recovers upon the subsequent discharging, portending the adsorption of I 2 (oxidation product) on the surface obscures part of the signal as well as the weakening structural order of the activated carbon. 45 However, there was no diffraction peak pointing to the I 2 adsorption owing to the limited content. X-ray photoelectron spectroscopy (XPS) was employed to evaluate the chemical changes on the surface of the AC/CFC cathode, in which two peaks appear at 632.7 eV and 621.0 eV associated with elemental I 0 in I 3d spectrum, visually proves the existence of adsorbed I 2 on the cathode at the fully charged state.…”
Section: Resultsmentioning
confidence: 99%
“…Type V non-ionic DESs, for instance, lack an ionic contribution and yet still exhibit DES characteristics. 23 We note here that the present review did not cover the use of type I and II DESs, but there are some examples reporting their application in batteries, [221][222][223] and they might represent viable alternatives. Also hydrophobic DESs have been reported which may overcome the viscosity issue associated with eutectics based on large quaternary ammonium salts and have better water-stability.…”
Section: Library Expansionmentioning
confidence: 98%